2007
DOI: 10.1111/j.1365-3083.2007.01994.x
|View full text |Cite
|
Sign up to set email alerts
|

Agonistic Anti‐4‐1BB Antibody Promotes the Expansion of Natural Regulatory T Cells While Maintaining Foxp3 Expression

Abstract: The engagement of the 4‐1BB (CD137) co‐stimulatory pathway promotes the activation and proliferation of conventional CD4+ T and CD8+ T cells, but the role of 4‐1BB co‐stimulation in CD4+ CD25+ regulatory T cells (Treg) is less clear. In particular, whether 4‐1BB stimulation affects the expression of Foxp3, a master gene for Treg, is unknown. This study demonstrates that co‐stimulation of 4‐1BB engaged by an agonistic antibody promotes the proliferation of Treg in a dependent manner of low‐concentration interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 24 publications
(26 reference statements)
1
48
2
Order By: Relevance
“…Our results do not support other data that have recently reported that signals through 4-1BB may inhibit Treg (32). On the contrary, more reliable data have been published suggesting that signals through 4-1BB may serve in a rather agonistic way (33)(34)(35). The exact mechanisms particularly in in vivo systems may be difficult to assess because 4-1BB has been demonstrated to be a potent stimulator particularly for conventional CD8 + T cells as well.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results do not support other data that have recently reported that signals through 4-1BB may inhibit Treg (32). On the contrary, more reliable data have been published suggesting that signals through 4-1BB may serve in a rather agonistic way (33)(34)(35). The exact mechanisms particularly in in vivo systems may be difficult to assess because 4-1BB has been demonstrated to be a potent stimulator particularly for conventional CD8 + T cells as well.…”
Section: Discussioncontrasting
confidence: 99%
“…This may be relevant considering that 4-1BB signaling can modulate the activation of CD4 + CD25 + Treg (34,35). It has been shown that the peripheral Treg pool comprises a complex mixture of Treg subpopulations (37) with the major classification into thymus-derived nTreg and peripherally iTreg.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CTLA-4 and PD-1, expression of 4-1BB and KLRG1 has been associated with enhanced Treg function (17,18). In each case, we found that combination blockade of the CTLA-4 and PD-1 pathways significantly decreased the fraction of Tregs expressing the relevant activation marker (Fig.…”
Section: Combination Coinhibitory Receptor Blockade Decreases Expressmentioning
confidence: 63%
“…The TNFRSF members GITR and OX40, which we observed to be expressed by Tregs ( Figure 1A), affect Treg activity and proliferation (21)(22)(23)(24)(25)(26)(27). There are also reports that stimulation of Tregs by 4-1BB can modulate both activity and proliferation of these cells (28,29). Furthermore, stimulation of CD4 + FoxP3 -cells by TNFRSF member CD27 (also known as TNFRSF7) has been reported to induce FoxP3 expression (30).…”
Section: Tnfr25 Is Highly Expressed By Tregs To Our Knowledge Therementioning
confidence: 65%